Religious Coping: Exploring the Resilience of Covid 19 Survivors - Zuhdiyah, Zuhdiyah (International Journal of Education Research and Development, 2023)
The purpose of this study is to investigate adult religious coping strategies throughout the COVID-19 pandemic's quarantine phase. In-depth semi-structured interviews with thirteen adult COVID-19 survivors, ages forty to sixty, were undertaken. Open-ended questions on the state of the COVID-19 sickness, the psychological state, and the religious coping mechanisms used up until the point of cure were posed to the respondents. The information was categorized using thematic analysis. Three adult coping strategies—positive thinking, positive activity, and yielding to God—are shown by the classification results. According to this research, the respondent experiences resilience and serenity when coping with the COVID-19 virus when they practice good religious coping. This study demonstrates how adult respondents manage to endure till they heal, but additional investigation is required to comprehend how religious coping is employed by populations that are more vulnerable to pressures.